Suits and Uniforms - Hasan Kösebalaban (International Institute of Islamic Thought, 2004)
Philip Robins contends that Turkish foreign policy has faced four challenges in four distinct periods of its history: (1) consolidating the emergent Turkish Republic through external recognition (1930s), (2) remaining neutral during the Second World War (1940s), (3) confronting the challenge of Soviet expansionism (the cold war era), and (4) responding to the end of bipolarity (post-cold war era). Robins examines these foreign policy issues in the last period. The main thesis of this work is threefold: First, Turkey is a status quo power in the way that its foreign policy elites have fastened their thinking and practice to the framework of “the sanctity of borders, of states, of multilateral institutions and of norms of conduct, even when it became clear that systemic changes had rendered some of these continuities no longer tenable” (p. 6). Second, Turkey continues to be firmly oriented westwards in terms of its foreign relations, which are characterized by its strong commitment to NATO as well as its desire to join the European Union (EU). Finally, Turkish foreign policy has been characterized more by “caution than daring,” quoting Malik Mufti. Despite the increase in its power relative to its neighbors, Turkey has avoided an interventionist foreign policy by emphasizing the formation of multilateral frameworks for conflict resolution. Robins defends these arguments by analyzing the international systemic and domestic politics context in which Turkish foreign policy is ...